2021
DOI: 10.3390/ani11040973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Enrichment on the Brain and on Learning and Cognition by Animals

Abstract: The humane treatment of animals suggests that they should be housed in an environment that is rich in stimulation and allows for varied activities. However, even if one’s main concern is an accurate assessment of their learning and cognitive abilities, housing them in an enriched environment can have an important effect on the assessment of those abilities. Research has found that the development of the brain of animals is significantly affected by the environment in which they live. Not surprisingly, their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…That a spatially more complex rearing environment results in improved spatial skills is supported by previous research 13 , 15 , 16 , 32 , with possible links to neural activity in the hippocampus 17 , 18 . However, the shorter latency to solve the detour task could also be linked to a generally improved ability to solve problems as a consequence of living in a more enriched environment (reviewed by Zentall 50 ). It is also possible that the usage of different variants of resources could have led to a positive feed-back loop whereby positive experiences from choosing different resource types resulted in a more optimistic outlook, as reported in animals living in more enriched or spatially complex environments 13 , 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That a spatially more complex rearing environment results in improved spatial skills is supported by previous research 13 , 15 , 16 , 32 , with possible links to neural activity in the hippocampus 17 , 18 . However, the shorter latency to solve the detour task could also be linked to a generally improved ability to solve problems as a consequence of living in a more enriched environment (reviewed by Zentall 50 ). It is also possible that the usage of different variants of resources could have led to a positive feed-back loop whereby positive experiences from choosing different resource types resulted in a more optimistic outlook, as reported in animals living in more enriched or spatially complex environments 13 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the shorter latency to solve the detour task could also be linked to a generally improved ability to solve problems as a consequence of living in a more enriched environment (reviewed by Zentall 50 ). It is also possible that the usage of different variants of resources could have led to a positive feed-back loop whereby positive experiences from choosing different resource types resulted in a more optimistic outlook, as reported in animals living in more enriched or spatially complex environments 13 , 50 . This could explain the chicks’ higher likelihood of exploring a novel environment as well as their shorter latency to find their way out of the box in the detour task.…”
Section: Discussionmentioning
confidence: 99%
“…Learning has been suggested as one of the most important factors for a farm animal when adapting to changing routines, social mixing and new resources in the production system . For many animal species, living in a more complex environment has been shown to facilitate learning and associated brain functions (see review by Zentall (2021)). Seeking is reported to be an important underlying factor promoting learning ability (Alcaro et al 2007), while fearfulness is seen to have inconsistent influences on learning (Krause et al 2006; de Haas et al 2017b;a).…”
Section: Increased Seeking Of Rewardsmentioning
confidence: 99%
“…EE can not only alleviate or even prevent cognitive dysfunction in normal aging [ 22 ] but can also counteract cognitive deficits caused by early-life stress [ 23 ]. The mechanisms by which EE ameliorates cognitive deficits, at least in part, were through improvements in neuroinflammation, oxidative stress, and mitochondrial function, as well as increases in hippocampal synaptic plasticity [ 24 26 ]. Our preliminary results suggested that cognitive impairment in aging offspring resulting from MSD can be alleviated by long-term EE [ 9 ].…”
Section: Introductionmentioning
confidence: 99%